PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN DINAS SOSIAL KABUPATEN BULELENG - Kadek Dwi Parmita,; Putu Ayu Anggya Agustina, (Juremi: Jurnal Riset Ekonomi, 2025)
This research is necessary to determine the extent of the effect of SIA on the financial recording of the Social Service of Buleleng Regency. A data accumulation strategy was employed quantitatively using a questionnaire. The data analysis method used is simple linear regression statistical analysis. The partial test analysis (T) produces a sig value (0.000) < alpha (0.005), indicating that SIA can influence the financial recording of the Social Service of Buleleng Regency. Furthermore, the coefficient test results show that 73.4% of the impact exists. Therefore, in order to evaluate the gaps and implement changes as soon as possible, the local government, and specifically the Social Service, must periodically monitor and audit the accounting information system in use. The agency should not only oversee staff performance but also monitor the information system being used